FASILITAS EKOWISATA BUKIT SULIGI DESA ALIANTAN KECAMATAN KABUN KABUPATEN ROKAN HULU - Tia Monika; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the description of existing facilities in the Bukit Suligi Tourism Object, Aliantan Village, Kabun District, Rokan Hulu Regency. This research method uses a qualitative method with a descriptive approach. Based on the results of research that has been done, the results show that the facilities available with 3 concept facilities are used, main facilities, supporting facilities and supporting facilities. The facilities at the Bukit Suligi Tourism Object are quite good such as the main facilities and supporting facilities, for supporting facilities it is very poor because they are not available at the Bukit Suligi Tourism Object. These supporting facilities are the obstacles in managing facilities at the Bukit Suligi Tourism Object. Keywords:  Aliantan Village, Object, Facilities